2022
DOI: 10.1007/s13412-022-00800-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brook trout in spatiotemporally separate locations using validated eDNA technology

Abstract: Brook trout are a species of conservation concern in Southwestern Ontario, Canada, and effective monitoring of their populations is crucial for making informed management decisions. Electrofishing is a traditional, yet invasive, method that allows for fish abundance estimation. Environmental DNA (eDNA) is an emerging molecular tool that presents a non-invasive alternative to electrofishing. This study was a collaborative effort between researchers in academia, industry, and an NGO, with the following objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…These filters were kept at room temperature until time of extraction. Smith-Root conducted a study showing that DNA did not degrade within 6 months at room temperature (Thomas et al, 2019) and these filters have also been used in other studies (Loeza-Quintana et al, 2020;Skinner et al, 2020;Banks et al, 2021;Nolan et al, 2022). These self-preserving eDNA filters are made of hydrophilic plastic which absorbs any remaining moisture into the package and preserves the DNA and prokaryotes via desiccation which has been shown as an effective preservation technique in other studies (Garcıá, 2011;Manzanera, 2021).…”
Section: Microbiome Analysesmentioning
confidence: 99%
“…These filters were kept at room temperature until time of extraction. Smith-Root conducted a study showing that DNA did not degrade within 6 months at room temperature (Thomas et al, 2019) and these filters have also been used in other studies (Loeza-Quintana et al, 2020;Skinner et al, 2020;Banks et al, 2021;Nolan et al, 2022). These self-preserving eDNA filters are made of hydrophilic plastic which absorbs any remaining moisture into the package and preserves the DNA and prokaryotes via desiccation which has been shown as an effective preservation technique in other studies (Garcıá, 2011;Manzanera, 2021).…”
Section: Microbiome Analysesmentioning
confidence: 99%
“…It is well-established that eDNA-based detection sensitivity is superior to conventional methods for fishes, which are the dominant taxa of interest in the eDNA literature (Hänfling & Lawson-Handley, 2021). Several studies have demonstrated the ability of eDNA-based methods to corroborate conventional survey data and further detect species not captured by conventional methods (Li et al, 2019;McDevitt et al, 2019;Nolan et al, 2023). Beyond simple presence/absence determination, eDNA has been used for semi-quantitative abundance assessment by establishing a correlation between population biomass and eDNA quantity or site occupancy across spatial replicates (Bourque et al, 2023;Evans et al, 2016;Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Once the reliability and repeatability of these technics are assessed, they can be embedded into management policies as it happened in the UK (reported by Handley et al, 2022). Despite the bias derived the variability in the spatio-temporal distribution of eDNA in the marine environment (reviewed by Rourke et al, 2021), its successful application in the detection of the brook trout (Salvelinus fontinalis) in spatially distinct sampling locations (i.e., small spatial scales: largest straight distance between two sites was 1.3 and 6.2 km) (Nolan et al, 2022) could potentially make it appropriate to be implemented in the management of SSFs (i. e., monitoring of sites at regional scales). Advancements in this field have been recently applied to abalone conservation: for example, to monitoring abundances of the northern abalone, H. kamtschtkana and detection of local genetic diversity of H. iris in New Zealand (Adam et al, 2022).…”
Section: Examples Of Genetic Methodologies Applied To Managementmentioning
confidence: 99%